Suvarnaprashana - Concept or Factual Practice of Ayurveda - Nagar, Rakesh Kumar; Ojha, Nisha (International Research Journal of Ayurveda & Yoga, 2022)
In antiquity, gold was perceived as an important medication with various favorable health effects. In an important book of Tao entitled Bauputz, the author, Hung Kir (283–363 ad) stated: “ingest gold to live a gold-like longevity”. These days, gold leaf, flake, or dust can be found adorning or being added to a variety of dishes and drinks. However, its sole function is that of a decorative accent. Gold, in all of its various medicinal forms, is considered to be the most potent component of many distinct herbo-mineral combinations in Ayurveda medicine. In pediatric populations, the usage of gold is recommended right from birth, in conjunction with honey and ghee; this process is known as Jatakarma in Ayurveda, while in the neonate and above age group, to promote health, strength, longevity, etc., Lehana is advised. Suvarnprashan is the name given to the practice of ingesting Suvarn Bhasma together with a mixture of Rasyana and Balya medicines on a regular basis for an extended period of time. Regular use of Suvarnprashan fosters the child’s overall growth. In addition to preventing infections, illnesses, and allergic reactions, it has a good influence on the child’s immune system. Suvarnprashan may accelerate the development of the brain, the central nervous system, and the generation of high-quality neurons, so that the future cognitive abilities of the child will be exceptional.